Pengembangan Ide "Point of View" dalam Dokumenter Televisi â€œTeduh Pelitaâ€ Edisi â€œRuang Mimpi, Rumah Singgahâ€ - Putri, Gusti Ayu Indyra; Basirun, Basirun (Jurnal Ilmiah Multimedia dan Komunikasi, 2023)
Health is a very important aspect in the life of everyone. Treatment of chronic diseases requires expensive medication costs and special handling. Based on this, Valencia Mieke Randa built a halfway house named Rumah Harapan Indonesia. Through Rumah Harapan Indonesia, she helps children and parents from various areas who do not haveplaces to live in Jakarta while undergoing treatment. All their needs, both materially and morally, are fully supported. Motivated by this story then the author decided to make a television documentary with the title "Ruang Mimpi, Rumah Singgah" with the aim to motivate and inspire people to do good and not hesitate to help others. The methods used by the author in this production are: field observations, approaches, and interviews with relevant sources, as well as audio-visual documentation. The author has a role as the producer, then the producer implemented producerâ€™s idea in creating this documentary program â€œTeduh Pelitaâ€ Edition of â€œRuang Mimpi, Rumah Singgahâ€. It could be concluded, first, that the writer as a producer has maximized the development of good ideas that can be seen in all sequences. The author optimized efforts to develop ideas, both point of view, motion graphics, and documentation photo frames in each sequence. Second, the producer applied conceptual planning after this documentary production was finished by combining good thoughts from the producer's idea development, visual development through the shot list by the program director, and scripts that support the language style by the script writer to make it easier to convey messages to the audience.